Significance of Tree Crown Diameter in Forest Mensuration - Srivastava, V. K.; Rai, A. M.; Dixit, R. K.; Oza, M. P.; Narayana, A.; Murty, E. S. (Indian Forester, 1998)
Mean crown diameter showed significant correlation with mean tree volume in man-made (Teak and Sal) and natural (dry and moist deciduous) forests. The value of correlation coefficient ("r") between mean crown diameter and mean tree volume was close to the value of "r" between DBH and mean tree volume. Regression equations were also developed and the predictive performance of the equations evaluated. It was concluded that mean crown diameter may be used to estimate mean tree vol ume in the above type of forests, as the growth of the tree is also reflected in the growth of the crown spread. Hence, it may be a good measure to estimate tree volume. It is therefore suggested that mean crown diameter may also be considered an important parameter in forest mensuration.